2012
DOI: 10.1093/eurjhf/hfs116
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐differentiation factor‐15 improves reclassification for the diagnosis of heart failure with normal ejection fraction in morbid obesity

Abstract: AimsThis study aimed to examine the incremental value of growth-differentiation factor-15 to N-terminal pro brain natriuretic hormone (NT-proBNP) levels for the diagnosis of left ventricular diastolic dysfunction (LVDD) and possible heart failure (HF) in morbidly obese patients. Method and resultsWe analysed data from 207 obese subjects [body mass index (BMI) 41 + 8 kg/m 2 ] with normal ejection fraction, LVDD, and symptoms and/or signs of HF (referred to as 'LVDD with possible HF', n ¼ 88) and with normal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
0
18
0
5
Order By: Relevance
“…Previous studies of the other groups have shown that the GDF-15 levels may partly represent an underlying pathophysiological mechanism for diastolic dysfunction. 16,17 Therefore, our data suggest that GDF-15 may potentially be an indicator of impairment in diastolic function, given its reasonable properties for detecting patients with parameters indicative of acute and chronically elevated filling pressures (i.e., E/E 0 ). …”
Section: Discussionmentioning
confidence: 84%
“…Previous studies of the other groups have shown that the GDF-15 levels may partly represent an underlying pathophysiological mechanism for diastolic dysfunction. 16,17 Therefore, our data suggest that GDF-15 may potentially be an indicator of impairment in diastolic function, given its reasonable properties for detecting patients with parameters indicative of acute and chronically elevated filling pressures (i.e., E/E 0 ). …”
Section: Discussionmentioning
confidence: 84%
“…Exclusion criteria were described elsewhere. 19, 20 Healthy normal weight control subjects (BMI 20–24.9 kg m −2 ) of similar age and gender distribution were also included. They were recruited by flyers and advertisements.…”
Section: Methodsmentioning
confidence: 99%
“…However, discrimination between HFREF and HFPEF using any biomarker or combination was moderate at best. In another study, however, GDF‐15 was able to improve reclassification of patients with possible HFREF, and was shown to outperform NT‐proBNP . In an elegant study, GDF‐15, a marker of fibrosis, was found in high concentrations in severely decompensated HF patients .…”
Section: Biomarkers In Heart Failurementioning
confidence: 97%